Jämförelse av två verktygsbaserade berikningar för gulbröstad kapucin (Sapajus xanthosternos) - Ebbestad, Marie (2021)
Golden-bellied capuchins (Sapajus xanthosternos) are small primates from Brazil known for their tool use abilities. They are an explorative species and are capable of several types of tool use. The capuchin population is under severe strain and is currently critically endangered, and as so there are conservation programmes in place for capuchins in zoos across the world. An important part of zoo animal welfare is enrichment, for both physical and psychological reasons, for example expression of natural behaviours. For this study, two variants of an enrichment device were created. The enrichment required using sticks as tools to get access to either honey or larvae in plastic tubes behind a wooden board. One variant was more difficult than the other, as the tubes were fastened at a steeper, downwards angle. The enrichment devices were presented simultaneously to golden-bellied capuchins at Parken Zoo in Eskilstuna, Sweden, with the aim to investigate whether one variant was preferred, and if the enrichment promoted welfare and expression of natural behaviours for the capuchins. The monkeys were observed with instantaneous scoring for general behaviours, and 1/0-scoring for enrichment-related behaviours. The capuchins were observed for eight days, with enrichment every second day and without enrichment every second day. Of the general behaviours, movement increased with enrichment, grooming and playful fighting decreased, and eating and foraging behaviour was not affected. The enrichment was well used and explored, and honey seemed to be the preferred feed type. The difficult variety was preferred over the easy variety, suggesting contrafreeloading as a possible reason. In total, four individuals successfully used the enrichment, of which three had not used anything similar before. The enrichment was concluded to have been effective as it elicited interest and tool use behaviour, and increased activity. Aside from enrichments increasing welfare, giving zoo animals an opportunity to learn an important natural behaviour such as tool use could also be important for future conservation plans.